2018
DOI: 10.1055/s-0037-1604285
|View full text |Cite
|
Sign up to set email alerts
|

Large In-mask Motion during Frameless Radiosurgery of a Brain Metastasis

Abstract: Frameless radiosurgery is now a common alternative to traditional in-frame treatment. Several dosimetric studies have reported small in-mask positioning inaccuracies during frameless radiosurgery. We present a case of an uncommonly large deviation in in-mask motion detected offline in a patient undergoing linear accelerator-based frameless radiosurgery. Our case illustrates how the use of a thermoplastic mask can lead to unacceptable setup errors for passive image-guided radiosurgery. The case underlines the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Relocatable thermoplastic mask systems are commonly used for patient immobilization during Stereotactic Radiosurgery (SRS) and Stereotactic Radiotherapy (SRT) treatments to reduce inter-and intra-fraction motion but do not eliminate it [1][2][3][4][5][6]. A study of 6DOF intrafraction motion reported up to 1.75mm of cranial translation and up to 1.6˚of cranial rotation within the thermoplastic mask [1].…”
Section: Introductionmentioning
confidence: 99%
“…Relocatable thermoplastic mask systems are commonly used for patient immobilization during Stereotactic Radiosurgery (SRS) and Stereotactic Radiotherapy (SRT) treatments to reduce inter-and intra-fraction motion but do not eliminate it [1][2][3][4][5][6]. A study of 6DOF intrafraction motion reported up to 1.75mm of cranial translation and up to 1.6˚of cranial rotation within the thermoplastic mask [1].…”
Section: Introductionmentioning
confidence: 99%